The night train to Berlin - Hudson, Melanie (Fiction writer) (London : One More Chapter, 2021)
"Paddington Station, present day. A young woman boards the sleeper train to Cornwall with only a beautiful emerald silk evening dress and an old, well-read diary full of sketches. Ellie Nightingale is a shy violinist who plays like her heart is broken. But when she meets fellow passenger Joe she feels like she has been given that rarest of gifts - a second chance. ... Paddington Station, 1944. Beneath the shadow of the war which rages across Europe, Alex and Eliza meet by chance. She is a gutsy painter desperate to get to the frontline as a war artist and he is a wounded RAF pilot now commissioned as a war correspondent. With time slipping away they make only one promise: to meet in Berlin when this is all over. But this is a time when promises are hard to keep, and hope is all you can hold in your heart."--Publisher.
Includes author interview, author's note, and reading group guide.
Keywords: World War, 1939-1945 -- Fiction; Friendship -- Fiction; Man-woman relationships -- Fiction; Women painters -- Fiction; Women violinists -- Fiction; War correspondents -- Fiction; Railroad travel -- Fiction; Berlin (Germany) -- Fiction; Historical fiction; Romance fiction